2014
DOI: 10.2514/1.a32716
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Quantification for Mars Entry, Descent, and Landing Reconstruction Using Adaptive Filtering

Abstract: Mars entry, descent, and landing (EDL) trajectories are highly dependent on the vehicle's aerodynamics and the planet's atmospheric properties during the day-of-flight. A majority of previous EDL trajectory and atmosphere reconstruction analyses do not simultaneously estimate the flight trajectory and the uncertainties in the models. Adaptive filtering techniques, when combined with the traditional trajectory estimation methods, can improve the knowledge of the aerodynamic coefficients and atmospheric properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 39 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The 3σ uncertainty bounds of the reconstructed positions for all three estimates encompass the independently estimated location. The UKF and adaptive filter have tighter bounds than the EKF, corroborating the expected outcomes when simulated data were analyzed by these estimators [3,35].…”
Section: B Trajectory Reconstructionsupporting
confidence: 71%
See 1 more Smart Citation
“…The 3σ uncertainty bounds of the reconstructed positions for all three estimates encompass the independently estimated location. The UKF and adaptive filter have tighter bounds than the EKF, corroborating the expected outcomes when simulated data were analyzed by these estimators [3,35].…”
Section: B Trajectory Reconstructionsupporting
confidence: 71%
“…The UKF estimates smaller velocity uncertainties than the adaptive filter in this case, but due to a lack of knowledge in the true state, it would be conjecture to attribute a physical rationale for this. Testing with simulated Mars EDL data in the past has shown that the adaptive filter actually had smaller uncertainties than the UKF [35].…”
Section: B Trajectory Reconstructionmentioning
confidence: 99%
“…For trajectory modeling and assessment of atmospheric characterization capabilities, similar entry conditions to the previously flown Mars Exploration Rovers have been used, with uncertainties extracted from [16]. During atmospheric entry, each ChipSat will perform attitude rate and acceleration measurements using an IMU comprising micro-electro-mechanical systems (MEMS) gyroscopes and accelerometers to reconstruct their trajectories.…”
Section: Mission Scenariomentioning
confidence: 99%
“…The ChipSat mass and reference area are modeled as 65 and 0.02 2 . The uncertainty ranges are taken from [16].…”
Section: A Trajectory Modelingmentioning
confidence: 99%
“…Future Mars explorations need the vehicles to land precisely at the prescribed locations to complete the missions, such as sample returns, high-mass entry, human explorations and so on. Mars entry phase is the most challenging part of Mars Entry, Descent and Landing (EDL) due to the complex aerodynamics and atmosphere properties (Dutta et al, 2014), which make the Mars entry dynamic model strongly nonlinear and time varying. Also, the entire Mars EDL phase only lasts a few minutes.…”
Section: Introductionmentioning
confidence: 99%